2013
DOI: 10.1096/fasebj.27.1_supplement.639.9
|View full text |Cite
|
Sign up to set email alerts
|

α‐linolenic acid reduces growth in four breast cancer cell lines with varying receptor expression in high and low estrogen environments

Abstract: Breast cancer differs in cell receptors which then determines effective treatments. Alpha‐linolenic acid (ALA)‐rich flaxseed oil reduced estrogen receptor (ER)+ cell growth at low and high estrogen (E2) but its effect is unclear in cells with varying ER, progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). Our objective was to determine in vitro the ALA and E2 effect on growth and membrane lipids of four breast cancer cell lines with varying ER, PR and HER2 status. Cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, COX-2 is the key enzyme in the biosynthesis of inflammatory mediators such as prostaglandins and leukotrienes; besides, the NF-κB pathway regulates the expression of pro-inflammatory cytokines (IL-1β, IL-6 and IL-8), anti-inflammatory factor (IL-10), and nitric oxide (NO). 21,27…”
Section: Functional Properties Of Csmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, COX-2 is the key enzyme in the biosynthesis of inflammatory mediators such as prostaglandins and leukotrienes; besides, the NF-κB pathway regulates the expression of pro-inflammatory cytokines (IL-1β, IL-6 and IL-8), anti-inflammatory factor (IL-10), and nitric oxide (NO). 21,27…”
Section: Functional Properties Of Csmentioning
confidence: 99%
“…In particular, COX-2 is the key enzyme in the biosynthesis of inflammatory mediators such as prostaglandins and leukotrienes; besides, the NF-κB pathway regulates the expression of pro-inflammatory cytokines (IL-1β, IL-6 and IL-8), anti-inflammatory factor (IL-10), and nitric oxide (NO). 21,27 In vitro cell experiments have shown that the ethanol extract of CS has significant lethality on human prostate cancer cells (PC-3), with an IC 50 value of 1.48 ± 0.72 μg mL −1 . 28 The concentrations of TNF-α and IL-10 were the lowest in Wistar rats fed with a CS ground meal; at the same time, compared to the high-fat group, the expression of NF-κB mRNA was relatively decreased after CS meal treatment.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
See 3 more Smart Citations